Analisis Kesulitan Pembelajaran Pai Dan Upaya Guru PAI dalam Meningkatkan Minat Belajar Siswa di SMAN 3 Sidoarjo - Maulidia Ilham; Febriarsita Eka (Journal on Education, 2024)
This research uses descriptive qualitative and data collection techniques through interviews and observations involving students and teachers at SMA Negeri 3 Sidoarjo. This research is strengthened by primary data and secondary data, this data is used as a source of information for the required research. This research aims to analyze the learning difficulties experienced by students in PAI subjects, and aims to find evaluation results in teachers' efforts to plan the process of subsequent teaching and learning activities. The results of this research are that the learning difficulties experienced by students occur depending on the learning media used by teachers in carrying out teaching and learning activities. Students feel bored and there is no interaction in the process of teaching and learning activities. The teacher's next effort is to carry out the learning process by adjusting student characteristics from the evaluation results. With these difficulties, teachers try to create discovery learning, namely students are more innovative in producing understanding of learning outcomes that are realized with digital smartphone-based content or learning. This article contributes to reviewing teachers' efforts to increase students' interest in learning in PAI subjects. Practical implications of using innovative digital-based learning media. This research has differences with the results of previous research.